Associations of Cerebral Small Vessel Disease and Chronic Kidney Disease in Patients With Acute Ischemic Stroke - Rentang Bi; Yanhao Wei; Pengcheng Li; Haokun Peng; Mohammad Alizadeh; Bo Hu; Yanan Li (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The relationship between chronic kidney disease (CKD) and cerebral small vessel disease has been inconsistently reported. In particular, there is a lack of research focusing on patients with acute ischemic stroke, a key area that could provide important insights into the brain–kidney connection. Methods AND RESULTS We established a large‐sample size, multicenter prospective cohort study (SMART [Cerebral Small Vascular Disease Registry Multicenter Clinical Trial]) across 13 subcenters in central China. All participants underwent long‐term, continuous renal function monitoring. CKD was assessed using the Kidney Disease Improving Global Outcomes criteria, defined as abnormal kidney function lasting for at least 3 consecutive months. Magnetic resonance imaging, including T2‐weighted and susceptibility‐weighted imaging, was used to detect markers of cerebral small vessel disease such as white matter hyperintensities, cerebral microbleeds, lacunar infarctions, and enlarged perivascular spaces. Multinomial, binomial, and ordinal logistic regression models were employed, adjusting for demographic, vascular, and stroke‐related factors. Among the 3909 patients with acute ischemic stroke (mean age 62 years, 35.3% female), 307 (7.9%) were diagnosed with CKD. Higher CKD risk grades were correlated with an increased burden of cerebral small vessel disease. After adjusting confounding factors, white matter hyperintensities (odds ratio [OR], 1.841 [95% CI, 1.413–2.400], P<0.001), lacunar infarctions (OR, 3.455 [95% CI, 2.314–5.158], P<0.001), and cerebral microbleeds (OR, 2.514 [95% CI, 1.976–3.199], P=0.005) were significantly more frequent in patients with CKD. Additionally, patients with CKD exhibited higher rates of cardiac embolism (OR, 1.405 [95% CI, 1.067–1.851], P=0.016) compared with other stroke causes. Conclusions Stroke clinicians should recognize CKD as a potentially independent and modifiable risk factor for cerebral small vessel disease.